Ingredients of Instrumental Meaning. (16th May 2017) - Rissman, Lilia; Rawlins, Kyle
Abstract: This paper presents an analysis of the English instrumental markers with and verbal use . As with other thematic roles, the semantic generalizations encoded by the role Instrument have been difficult to precisely characterize. In this study, we analyze the distinct semantic contributions of with and use, illuminating several properties of instrumental meaning. In particular, use specifies that the agent must act intentionally, which we formalize as universal quantification over possible worlds within a Montague‐style compositional framework. By contrast, with encodes a constraint whereby an instrument is a direct extension of the force initiated by the agent. This analysis is most consistent with theories in which thematic roles are clusters of event properties, rather than categories defined in terms of necessary and sufficient conditions; our analysis does not make use of Instrument as a primitive role.